A retrospective study demonstrating properties of nonvariceal upper gastrointestinal bleeding in Turkey - (:unkn) unknown (AVES, 2011)
Background/aims: Helicobacter pylori infection, non-steroidal anti-inflammatory drugs and peptic ulcer are considered as the major factors for upper gastrointestinal system bleeding. The objective of the study was to determine the sociodemographic and etiologic factors, management and outcome of patients with non-variceal upper gastrointestinal system bleeding in Turkey. Methods: Patients who admitted to hospitals with upper gastrointestinal system bleeding and in whom upper gastrointestinal endoscopy was performed were enrolled in this retrospective study. The detailed data of medical history, comorbid diseases, medications, admission to intensive care units, Helicobacter pylori infection, blood transfusion, upper gastrointestinal endoscopy, and treatment outcome were documented. Results: The most frequent causes of bleeding (%) were duodenal ulcer (49.4), gastric ulcer (22.8), erosion (9.6), and cancer (2.2) among 1,711 lesions in endoscopic appearances of 1,339 patients from six centers. Seven hundred and four patients were evaluated for Helicobacter pylori infection and the test was positive in 45.6% of those patients. Comorbid diseases were present in 59.2% of the patients. The percentage of patients using acetylsalicylic acid and I or other non-steroidal anti-inflammatory drug was 54.3%. Bleeding was stopped with medical therapy in 66.9%. Only 3.7% of the patients underwent emergency surgery, and a 1.1% mortality rate was determined. Conclusions: Patients with upper gastrointestinal system bleeding were significantly older, more likely to be male, and more likely to use non-steroidal anti-inflammatory drugs. Though most of the patients were using gastro-protective agents, duodenal and gastric ulcers were the contributing factors in more than 70% of the upper gastrointestinal bleeding. The extensive use of non-steroidal anti-inflammatory drug is a hazardous health issue considering the use of these drugs in half of the patients.
Keywords: Non-steroidal anti-inflammatory drugs; acetylsalicylic acid; gastrointestinal bleeding; gastrointestinal endoscopy; Helicobacter pylori; peptic ulcer; ENDOSCOPY